Lesion volume and location can be estimated by analysis of the new NIH Stroke Scale picture description - Melissa D. Stockbridge; Voss Neal; Shun Liu; Lindsey Kelly; Isidora Diaz-Carr; Joseph S. Kang; Andreia V. Faria; Argye E. Hillis (PLoS ONE, 2025)
In January 2024, the picture stimuli used to elicit language on the NIH Stroke Scale were updated. Descriptions elicited using the now-retired Cookie Theft picture are informative regarding the size and location of stroke. An important dimension of validation for the new stimuli is to demonstrate that the language patients produce when describing the new Precarious Painter picture that is now part of the NIH Stroke Scale is similarly informative. Participants included 62 patients with acute ischemic stroke (24 left and 38 right) compared with 10 control participants hospitalized following transient ischemic attack. Descriptions of the Precarious Painter image were analyzed for content and structure. Bilateral regions of interest were selected based on their role in language processing, and lesion volume and location were measured on diffusion-weighted imaging. Analyses of variance were used to contrast discourse performance across groups, and correlations between discourse characteristics and proportion of region lesioned were calculated. Patients with left hemisphere strokes included less content from the right side of the picture, F(2) = 7.4, p = 0.001, η 2 P = 0.19, than those in the other groups. Informational efficiency had a strong inverse relationship with extent of lesion to the left, but not right, IFG. Correlations between discourse variables and lesion locations were grossly consistent with those previously reported and evidenced relationships between discourse variables and the bilateral extended language network. Features of picture description that may be appraised without specialized training in communication, such as how many things a patient includes, their location, and the inclusion of inferences or summarizing statements in the description, provide insight into stroke location and severity. The samples elicited using the new Precarious Painter stimulus perform similarly to those elicited using the retired Cookie Theft stimulus.